2021
DOI: 10.1111/plb.13245
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma treatment induces abscisic acid production, reduces stomatal aperture and improves seedling growth in Arabidopsis thaliana

Abstract: Cold atmospheric pressure plasmas (CAPPs) have been widely used for pre‐sowing treatment in agriculture to accelerate seed germination; however, information on their application to pre‐transplant seedlings is scarce. The roles of the phytohormone abscisic acid (ABA) on guard cell aperture that control air exchange with the environment were investigated after CAPPs treatment. In this study, Arabidopsis thaliana seedling growth was evaluated under CAPPs treatment at different doses. Besides, the optimal growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Li et al [ 171 ] showed that NTP treatment of tomato seeds up-regulated transcription of 9-cis-epoxycarotenoid dioxygenase 1 ( NCED1 ) that conferred ABA accumulation in a respiratory burst oxidase homologue 1 ( RBOH1 )-dependent manner, leading to an improved tolerance to cold stress in tomato plants. In addition, a higher accumulation of transcripts from ABA signaling pathway genes was observed in 2-day-old Arabidopsis seedlings germinated from NTP-treated seeds, although their transcripts were significantly down-regulated after 4 days [ 163 ]. It has been proposed that NTP treatment accelerates ABA accumulation in the early growth stages and ABA regulates ROS and Ca 2+ concentrations to affect the stomatal aperture, which is associated with NTP-induced stimulation of seedling growth.…”
Section: Effects Of Plasma Treatment On Biochemical and Physiological...mentioning
confidence: 99%
“…Li et al [ 171 ] showed that NTP treatment of tomato seeds up-regulated transcription of 9-cis-epoxycarotenoid dioxygenase 1 ( NCED1 ) that conferred ABA accumulation in a respiratory burst oxidase homologue 1 ( RBOH1 )-dependent manner, leading to an improved tolerance to cold stress in tomato plants. In addition, a higher accumulation of transcripts from ABA signaling pathway genes was observed in 2-day-old Arabidopsis seedlings germinated from NTP-treated seeds, although their transcripts were significantly down-regulated after 4 days [ 163 ]. It has been proposed that NTP treatment accelerates ABA accumulation in the early growth stages and ABA regulates ROS and Ca 2+ concentrations to affect the stomatal aperture, which is associated with NTP-induced stimulation of seedling growth.…”
Section: Effects Of Plasma Treatment On Biochemical and Physiological...mentioning
confidence: 99%
“…Biotic stresses such as viral or fungal infections, or abiotic stress such as irradiation, salinity, heat, and cold always accelerates inner abscisic acid (ABA) accumulation in plants [ 107 , 114 ]. As it supposed that this technology will alleviate the stress effects of the plants, it has been perceived that γ-ray irradiation could accumulate abscisic acid (ABA) by upregulating the related genes, and such a generation of plant hormones would lead to the synthesis of ROS, and in return, the antioxidant enzyme system would be enhanced by the over-production of ROS which would maintain the optimal redox status in the plants.…”
Section: Ionizing Physical Seed Priming and The Underlying Mechanismsmentioning
confidence: 99%
“…This point is also supported by transcriptomic data that the indicate that the plant stimulatory effects are involved in the ABA signaling pathway [ 112 ]. The endogenous ABA and ROS may further control the stomata to mediate gas exchange and increase stress tolerance [ 114 ]. Then, it was found that stomatal conductance was markedly increased by γ-ray irradiation in garden pea ( Pisum sativum L), spinach ( Spinacia oleracea ), and okra ( Abelmoschus esculentus ) [ 105 ].…”
Section: Ionizing Physical Seed Priming and The Underlying Mechanismsmentioning
confidence: 99%
“…Thus, the GA-ABA ratio is an important factor that modulates the transition of seeds from dormancy to germination [176,194]. Recently, the plasma treatment of Arabidopsis seedlings was demonstrated to accelerate ABA accu-mulation at the early growth stages due to the expression of specific genes [195].…”
Section: Ros and Rns Interactionsmentioning
confidence: 99%
“…The strict control of stomatal movements, balanced by ROS and NO, is essential in drought-tolerant plants [200]. Stomatal movement is directly related to the concentrations of ABA, ROS, and NO [195]. Traditionally, ABA is an important plant hormone that is traditionally associated with responses to water stress and acts as an upstream regulator, inducing the synthesis of NO.…”
Section: Rons Involvement Under Abiotic Stress Conditionsmentioning
confidence: 99%